Phytochemical Analysis with Antioxidant and Cytotoxicity Studies of the Bioactive Principles from Zanthoxylum capense (Small Knobwood) - Bodede, Olusola; Shaik, Shakira; Singh, Moganavelli; Moodley, Roshila (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Zanthoxylum capense (small knobwood) is a South African species known for a wide range of anecdotal uses. However, there is a dearth of information on its phytoconstitutional make-up, specifically its knobs, with only a few reports on the bioactive compounds that could justify its ethnomedicinal use. Objectives: This work aimed to identify the active principles in Z. capense and evaluate their cytotoxicity against breast cancer tumor cells. Method: Extracts from the stem bark, knobs and leaves were purified using chromatographic methods and characterized using spectroscopic techniques. Cytotoxicity of isolated compounds was evaluated on mammalian MCF-7, Caco-2 tumor cell lines and HEK295, a normal kidney cell line. Results: The following compounds were isolated from the plant: a quaternary benzophenanthridine-type alkaloid (chelerythrine) along with its alkanoamine derivative (6-hydroxydihydrochelerythrine), an indolopyridoquinazoline alkaloid (rutaecarpine), an alkyl p-coumaric acid ester (dodecyl-trans-p-coumarate), a lignan (sesamin), a flavanol (catechin), two triterpenoids (lupeol and sitosterol) and two pigments (pheophytin a and lutein). In the cytotoxicity study, all tested samples decreased the viability of the MCF-7 tumor cells by at least 23% at concentration 1 μg mL-1 and Caco-2 tumor cells by at least 15% at concentration 5 μ g mL-1 but a mild toxic effect on HEK295 across the tested samples. Results: The following compounds were isolated from the plant: a quaternary benzophenanthridine-type alkaloid (chelerythrine) along with its alkanoamine derivative (6-hydroxydihydrochelerythrine), an indolopyridoquinazoline alkaloid (rutaecarpine), an alkyl p-coumaric acid ester (dodecyl-trans-p-coumarate), a lignan (sesamin), a flavanol (catechin), two triterpenoids (lupeol and sitosterol) and two pigments (pheophytin a and lutein). In the cytotoxicity study, all tested samples decreased the viability of the MCF-7 tumor cells by at least 23% at concentration 1 μ g mL-1 and Caco-2 tumor cells by at least 15% at concentration 5 μ g mL-1 but a mild toxic effect on HEK295 across the tested samples.
Keywords: ethnomedicine